Pengaruh Kualitas Pelayanan Pajak Dan Pemahaman Peraturan Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Pratama Maumere - Maria Imakulata; Wihelmina Mitan; Yoseph Darius P. Rangga (Universitas Maritim AMNI Semarang, 2023)
The purpose of this study is to analyze the effect of tax service quality and understanding of tax regulations on individual taxpayer compliance. This research is a quantitative research with an associative approach. The population in this study is all taxpayers who report to the Maumere Pratama Tax Service Office amounting to 23,931 taxpayers. The sample in this study used the slovin formula with a total of 100 taxpayers. Data collection was carried out through the distribution of questionnaires to respondents, where the research instrument used the Likert scale. Data analysis techniques using multiple linear regression analysis models with the help of SPSS programs, descriptive statistics, data quality tests and classical assumption tests. The results of the study are known that the quality of tax services and understanding of tax regulations partially or simultaneously affect the compliance of individual taxpayers.